Pemantauan Secara Realtime Output Panel Surya Dengan Penambahan Reflektor - Saputra, Tomy; Gusa, Rika Favoria; Asmar (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
Indonesia is a country with a tropical climate so it is very suitable to develop solar panels as a producer of electrical energy. To increase the output produced by solar panels, it is done by adding reflectors on both sides of the panel opposite each other whose tilt angle can be adjusted. In addition, to facilitate the monitoring, storage, and retrieval of data, a website was built to be able to monitor data in real time, so that data can be accessed without the obstacles of distance and time. Therefore, in this study, a solar panel output monitoring system was built with the addition of a reflector in real time. Based on the results of monitoring during the study, it was found that solar panels installed with reflectors with variations in angles of 60°, 70°, and 80° on both sides had a higher output than solar panels without reflectors.